Development of Booklet Media to Improve Career Understanding of Grade IX Students - Paranisa, Mitra Bunga; Dalimunthe, Raudah Zaimah; Wibowo, Bangun Yoga (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
Development of Booklet Media to Improve Career Understanding of Grade IX Students. This study aims to develop a booklet media to enhance career understanding among ninth-grade students at SMP Negeri 2 Waringinkurung. The booklet is Designed to present career information in a structured, clear, and easy-to-understand manner. The method used is the Research and Development (R&D) model with the ADDIE stages (Analysis, Design, Development, Implementation, and Evaluation). In the Analysis stage, the students' needs were identified to Design a product relevant to their career Development. The results of the feasibility test showed positive evaluations from subject matter experts, language experts, and practitioners, with an average score of 92%, indicating high feasibility. A product trial involving 42 students resulted in a feasibility score of 81%, categorized as very feasible. The effectiveness test using N-Gain revealed an N-Gain score of 0.8886 and an N-Gain percentage of 88.86%, indicating a significant improvement in career understanding. Overall, this media booklet has been proven to be effective and can be used as an important tool for helping students plan their careers in the future. The Development of this booklet also provides a valuable alternative for career education at the junior high school level.Keywords: Booklet, Carrier, Media, Career Understanding.